The Effect of Product Innovation and Market Orientation on Performance Muhammadiyah Da'wah Institute Marketing - PRABOWO, Eko; ZEN, Muhamad (Journal of Entrepreneurial and Business Diversity, 2023)
Purpose:Muhammadiyah da'wah is included in da'wah in the reform era because da'wah in the reform era Muhammadiyah began to get a good response, it is very important to have a strategy, management and management of da'wah to advance da'wah. The purpose of this research is to identify the techniques and tactics of Indonesian Muhammadiyah da'wah.Methodology:This study is qualitative research with data collection methods through observation. Data analysis in this study used a qualitative descriptive method with a sociological approach.Findings:The study results show that Muhammadiyah da'wah's methods generally include the da'wah method of wisdom, good advice, and good dialogue. Muhammadiyah's da'wah strategy is to prioritize Islamic teachings in accordance with the Shari'ah, form a Hajj ritual guidance institution, build a culture of dialogue, and foster young generations, mass media preaching, cultural preaching, and preaching community empowerment in the fields of education, economy, social and health.Implication:Da’wah in the marketing strategy of Muhammadiyah da'wah institutions in the form of selling Muhammadiyah products such as water and noodles to the community by treating them with quality ingredients so that they do not cause disease implications that occur, and the selling price is not too high and can still be reached by consumers as well as mineral water in general. The purpose of this Muhammadiyah product is to uphold the Islamic religion so that an actual Islamic society is realized. By offering Muhammadiyah products, they can introduce Muhammadiyah preaching to consumers by buying Muhammadiyah products.